The functional exercise capacity in patients with bipolar disorder versus healthy controls: A pilot study. Issue 1 (30th September 2015) - Vancampfort, Davy; Wyckaert, Sabine; Sienaert, Pascal; De Hert, Marc; Stubbs, Brendon; Buys, Roselien; Schueremans, Ans; Probst, Michel
Abstract: The aim of the current study was to compare the functional exercise capacity of patients with bipolar disorder with age-, gender- and body mass index (BMI)-matched healthy controls. Thirty patients (16 ♂, 40.8±11.6 years) and healthy controls (16 ♂, 40.5±10.8 years) were included. All participants performed a 6-min walk test to assess the functional exercise capacity and completed the International Physical Activity Questionnaire. Patients were screened for psychiatric symptoms using the Quick Inventory of Depressive Symptomatology and Hypomania Checklist-32. Results demonstrated that patients with bipolar disorder demonstrated a significantly poorer functional exercise capacity (590.8±112.6 versus 704.2±94.3 m). A backward stepwise regression analyses showed that the level of depression and existing foot or ankle static problems and back pain before the test explained 70.9% of the variance in the distance achieved on the 6-min walk test (functional exercise capacity). The current study demonstrates that foot and back pain appear to be important negative predictors of functional exercise capacity in patients with bipolar disorder. Physical activity interventions delivered by physical therapists may help ameliorate pain symptoms and improve functional exercise capacity. Highlights: Patients with bipolar disorder have a lower functional exercise capacity than healthy controls of similar age, gender and body mass index. Foot pain, low back pain and depressive symptoms were the largest significant independent predictors and explained 70% of the variance in functional exercise capacity of patients with bipolar disorder. Improving the functional exercise capacity and physical activity participation should be considered as key targets in the multidisciplinary treatment of patients with bipolar disorder. Exercise interventions that ameliorate pain can be devised by physical therapists and may be pivotal in improving the functional outcome and quality of life of patients with bipolar disorder.